PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM PERJANJIAN PEMBIAYAAN KENDARAAN BERMOTOR RODA DUA BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Ruslan, Milawartati T. (Katalogis, 2016)
The problem studied were how the legal protection to business entities in affecting standar clauses and how the legal protection to customers in motor cycle sale-purchase pursuant to Law Number 8 Year 1999 about Customer Protection were. The purpose of the research was to identfy and analyze the legal protection toÂ business entities in ffecting standard clauses and how the legal protection to customers in motor cycle sale-purchase pursuant to Law Number 8 Year 1999 about Customer Protection. It was a normative research based on Primary Legal Material, Secondary Legal Material and Tertiary Legal Material. It was concluded that the legal protection to customer was based on prevailing law and regulation, sale-purchase contract agreement and judicial protection where the customers can exercise their right through government judicial institutions through litigation and non-government judicial institution through non-litigation.